Thiamine status of feedlot cattle fed high concentrate diet - Karapinar, T.; Dabak, M.; Kizil, O. (Elsevier Science Inc, 2010)
[Abstract Not Available]
Keywords: polioencephalomalacia; transketolase; vitamin B1